Accelerated aging effects on carbon fiber PEKK composites manufactured by hot compression molding - Mazur, Rogério L.; Cândido, Geraldo M. [UNESP]; Rezende, Mirabel C.; Botelho, Edson C. [UNESP] (SAGE Publications, 2016)
The accelerated aging effects on mechanical properties of carbon fiber-reinforced polyetherketoneketone (PEKK) thermoplastic composites are reported. Ultraviolet (UV) radiation and moisture absorption may induce property changes that weaken the polymeric matrix and/or deteriorate the matrix fiber interface by debonding or microcracking. The aim of the present work is to correlate the influence of the accelerated aging effects on compression and shear properties of carbon fiber-reinforced PEKK thermoplastic composite manufacturing by hot compression molding. The hot compression molding process was shown to be a good alternative for producing the thermoplastic composite, with an appropriate impregnation. The UV radiation/condensation conditioning effect did not show significant influence on shear strength properties. However, the most significant change was observed in the compression and shear strength after the specimens were submitted to the hygrothermal conditioning, which presented a marked increase. This behavior suggests an antiplasticization effect.
Keywords: Accelerated aging effects; hot compression molding; PEKK